PRANKING AS A SPECIFIC FORM OF POLITICAL COMMUNICATION - Авксентьєв, О. Л. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
The article presents the phenomenon of pranking as a specific form of political communication. The evolution and the stages of this phenomenon’s development are traced since the end of the 19th century when telephones appeared. The emphasis is placed on the fact that it is the two-stage building of the pranking model that contributes to the entrenchment of pranking in the political culture of society. A certain connection between the pranking development and the achievements of the scientific and technological progress in the field of mass media is revealed. It is shown how, with the advent of the Internet, pranking turns into an important segment of social communications, and prankerism – into nearly a separate profession, how the circle of “victims” of prankerism expands at the expense of well-known politicians and leaders of certain states, which in its turn affects the formation of public opinion on these objects of prankerism.It is noted that the result of the pranking development consists in complicating and diversifying the circulation of political information between the various elements of the political system, between the political and social systems, between the administered and the administering, and between the politically active and passive segments of the population. By way of illustration, a schematic structure of pranking is provided. It is concluded that it is necessary to focus the attention of political and other scientists on studying this phenomenon and highlighting its positive and negative aspects. The problem of the consequences of pranking, both in terms of the development of political communication, the operating mode of the political system of a country as a whole and of its individual parts, and in terms of the internal and external state security, emerges full blown. The question is raised as to what conclusions political leaders themselves should draw in order not to take the bait of prankers and not to lower the electoral rating among the population of their country.